Matematika: Hakikat dan sejarah matematika - Farikha, Tsania Nur (Maliki Interdisciplinary Journal, 2024)
Mathematics is knowledge about quantity and space, a branch of knowledge that is sequential, orderly and exact. Mathematics helps humans to accurately interpret various kinds of ideas and conclusions. Mathematics has an important role in our understanding of the world and as a tool for making progress in various fields. Mathematics is always present and embedded in any field, whether social, economic or religious, so that mathematics is a reflection of human civilization on this earth. So, it is not wrong if the history of mathematics is the history of human civilization. This history starts from ancient times to the 21st century and advanced mathematics, which tells about the discoveries, experiments, hard work and creative thinking of mathematicians all over the world.